Evaluation of the Design for the Construction of a 100 kW Micro Hydropower Plant (PLTMH) Utilizing Condenser Cooling Water Discharge at a 2×25 MW Coal-Fired Power Plant (CFPP) - Khoeruz zaman; Jaka Windarta; Sulistyo (Universitas Muhammadiyah Sidoarjo, 2026)
The utilization of residual energy within existing power plant systems represents a promising pathway to enhance energy efficiency and support decarbonization without requiring additional fuel consumption. This study evaluates the feasibility of integrating a micro-hydropower (MHP) system into the condenser cooling water discharge of a coal-fired power plant (CFPP) in Indonesia. A quantitative techno-economic assessment framework is employed, incorporating hydraulic analysis, annual energy production estimation, discounted cash flow (DCF) evaluation, environmental impact assessment, and sensitivity analysis. The results indicate that an average discharge of 1.20 m³/s and an effective head of 8.73 m can generate an actual power output of 77.37 kW, corresponding to an annual electricity production of 610.01 MWh. Economic evaluation shows strong feasibility, with a Net Present Value (NPV) of approximately IDR 3.9–4.0 billion, an Internal Rate of Return (IRR) of about 27%, a Levelized Cost of Energy (LCOE) of approximately IDR 725/kWh, and a payback period of 3.6 years. Sensitivity analysis reveals that capacity factor and discount rate are the most influential parameters affecting LCOE and NPV, respectively, while the system remains financially robust under ±10% variations. From an environmental perspective, the system can reduce carbon emissions by approximately 518 tons CO₂ per year without additional fuel consumption. Compared to conventional river-based micro-hydropower systems, the proposed approach offers higher operational stability, lower resource dependency, and reduced investment risk due to the utilization of continuous industrial flow and existing infrastructure. Overall, the findings demonstrate that integrating micro-hydropower into condenser cooling systems is a technically feasible, economically competitive, and low-risk strategy for improving energy efficiency and supporting incremental decarbonization in thermal power plants. The study contributes to the advancement of infrastructure-based energy recovery approaches and provides a practical framework for industrial-scale implementation.